Children’s well-being: Parental awareness on child internet addiction - Abdul Rashid, Abdul Aziz; Amin Al-Haadi, Shafie; Mohd Azrin, Mohd Nasir; Mohd Ropizam, Mohamad Zainun; Sukandar, Warlan; Nur Ain, Mustafar (Human Resource Management Academic Research Society (HRMARS), 2024)
Internet addiction among children has become a global health problem, including Malaysia. It raised public awareness of its increasing number. Most of the internet addiction risk factors relate to parents and their awareness regarding this issue. Therefore, this study was done to explore family awareness of child’s internet addiction and to identify the role of the family in overcoming internet addiction among children. This is a qualitative study using a scoping review design. The articles were obtained from the Academic Search Premier@EBSCOhost university database published from 2015 to 2023. A total of 38 articles were selected from the EBSCO-Host together with other relevant and significant articles from earlier years. Findings revealed that family awareness in term of understanding role of family members (parent’s role, sibling’s role, child’s role) is very important in facing internet addiction among children. Besides that, there are five elements in managing child internet addiction which include controlling and monitoring children's internet use, limiting time and space in children's internet use, the concept of psychological reward and punishment in internet use, application of moral and spiritual values, and joint involvement of parents and children in social activities. In conclusion, this study can be a guidance to the involved party such as educators or community in dealing and helping the family or parents who are facing with the issue of child’s internet addiction.